(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to use the brainstorming strategy using the “poll every where” tool in teaching the preparation skill in volleyball to the second Rusafa Education team for the primary stage. The researcher deliberately selected the research sample in a random way from the teams of the six Baghdad Education Directorates, and the research community was composed of From 90, Player: 30 players were chosen to conduct research on them and were divided into two groups, experimental and control. After applying the educational program and conducting post-tests for the two groups, the researcher concluded that there were significant differences in the results of the post-tests for the two groups and in favor of the experimental group. The researcher recommended the use of virtual classes in their educational programs because of their positive role. On learning outcomes, the researcher recommended that the brainstorming strategy be used using the “poll everywhere” tool in other skills and other sports.